2022
DOI: 10.3390/jof8070737
|View full text |Cite
|
Sign up to set email alerts
|

New-Generation Sequencing Technology in Diagnosis of Fungal Plant Pathogens: A Dream Comes True?

Abstract: The fast and continued progress of high-throughput sequencing (HTS) and the drastic reduction of its costs have boosted new and unpredictable developments in the field of plant pathology. The cost of whole-genome sequencing, which, until few years ago, was prohibitive for many projects, is now so affordable that a new branch, phylogenomics, is being developed. Fungal taxonomy is being deeply influenced by genome comparison, too. It is now easier to discover new genes as potential targets for an accurate diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 184 publications
0
17
0
Order By: Relevance
“…Metagenome sequencing has several advantages, including the fact that: (i) the huge amount of information may enable identification up to strain level; (ii) it allows for simultaneous and PCR bias-free detection of fungal, oomycete and prokaryotic strains; (iii) little to no a priori genetic information about the pathogen causing the plant disease is required ( Quince et al., 2017 ; Sekse et al., 2017 ; Semenov, 2021 ; Aragona et al., 2022 ); and (iv) the technique allows for the recovery of genomes from yet uncultured microorganisms ( Duan et al., 2009 ; Piombo et al., 2021 ). Especially for detection of viral plant pathogens, metagenomic approaches are useful, as viruses do not have universal genes that are targeted in amplicon sequencing, and as mentioned above, the metagenomic approach doesn’t require prior knowledge, enabling detection of plant pathogens that are yet unknown ( Adams et al., 2009 ; Roossinck et al., 2015 ; Adams and Fox, 2016 ).…”
Section: Nucleic Acid Sequencing Methodsmentioning
confidence: 99%
“…Metagenome sequencing has several advantages, including the fact that: (i) the huge amount of information may enable identification up to strain level; (ii) it allows for simultaneous and PCR bias-free detection of fungal, oomycete and prokaryotic strains; (iii) little to no a priori genetic information about the pathogen causing the plant disease is required ( Quince et al., 2017 ; Sekse et al., 2017 ; Semenov, 2021 ; Aragona et al., 2022 ); and (iv) the technique allows for the recovery of genomes from yet uncultured microorganisms ( Duan et al., 2009 ; Piombo et al., 2021 ). Especially for detection of viral plant pathogens, metagenomic approaches are useful, as viruses do not have universal genes that are targeted in amplicon sequencing, and as mentioned above, the metagenomic approach doesn’t require prior knowledge, enabling detection of plant pathogens that are yet unknown ( Adams et al., 2009 ; Roossinck et al., 2015 ; Adams and Fox, 2016 ).…”
Section: Nucleic Acid Sequencing Methodsmentioning
confidence: 99%
“…In recent decades, taxonomic studies of fungi have advanced significantly through the use of integrative (polyphasic) taxonomy, a method that combines genetic data (such as fungal DNA barcoding and phylogeny), physiological and biochemical features, ecological roles, and reproductive biology (when possible) to delimit species [ 31 , 101 , 102 , 103 ]. Recent advances in sequencing technology (metabarcoding, metagenomics, HTS, and WGS) have led to a greater understanding of fungal diversity, taxonomy, ecological roles, missing lineages, and fungal communities [ 64 , 104 , 105 , 106 , 107 ]. For example, metagenomics, specifically through metabarcoding and shotgun metagenomics, is instrumental in studying microbial communities.…”
Section: Approaches In Taxonomy and Classificationmentioning
confidence: 99%
“…As a result, some studies have suggested the utility of incorporating microbial indexes into soil and ecosystem health assessment protocols (Andrews et al, 2004; Nunes et al, 2021). However, our knowledge about microbial succession pattern and their driving mechanism was comparatively poor in contrast with the plant succession due to the lagging development of technological methods (especially the next‐generation sequencing technologies) (Akaçin et al, 2022; Aragona et al, 2022; Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%